THE INDENTITY OF THE DOCTORAL STUDENT IN THE IMPLEMENTATION OF THE NEW DOCTORAL STUDENT MODEL IN LATVIA - Kudeikina, Inga; Mihailovs, Ivans Jānis (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
The article analyzes issues related to the introduction of the new doctoral study model in Latvia. The transition affects several dimensions - institutional, quality, funding, etc., while the identity of the doctoral student is of great importance. Qualitative scientific research is of interest not only to the doctoral student himself, but also to the university and the country as a whole. The authors of the article believe that the new identity of the doctoral student can be strengthened by emphasizing the understanding of his duties and responsibilities, including so that the results of the doctoral student's scientific research work are used, realized and contribute to the development of the country. economy (and not only).